Preparation method of power cable with high-performance insulator material

By selecting environmentally friendly high-performance raw materials such as modified XLPE, nano-reinforced thermoplastic elastomers and flame retardants, and using precision process conditions, the problem of insufficient performance of power cable insulation materials in specific applications is solved, and the preparation of high-performance insulator materials is realized, which significantly improves the high temperature resistance, flame retardancy and wear resistance of the cable.

CN119708715APending Publication Date: 2025-03-28ZHONGXIN CABLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411950331.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing power cable insulation materials have insufficient performance in certain specific applications, especially in terms of high temperature resistance, flame retardancy and wear resistance.

Method used

Environmentally friendly high-performance raw materials such as modified XLPE, nano-reinforced thermoplastic elastomer (TPE-N) and flame retardant compositions are used, and high-performance insulator materials are prepared by precisely controlling their proportions and process conditions, including chemical crosslinking reactions, ultrasonic dispersion technology and precision temperature control.

Benefits of technology

It significantly improves the high temperature resistance, flame retardancy and wear resistance of power cables, complies with environmental protection standards, and maintains excellent electrical insulation performance and mechanical strength in high temperature and harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708715A_ABST
    Figure CN119708715A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cable preparation, and discloses a preparation method of a power cable with a high-performance insulator material, comprising the following steps: step A, selecting raw materials; step B, preparation process: premixing the raw materials in a high-speed mixer, then carrying out melt blending and extrusion granulation through a twin-screw extruder at 180-230 DEG C, and carrying out vacuum heat treatment at 120-150 DEG C for 2-3 hours to remove residual volatile matters and optimize the performance of the material; and step C, preparing the power cable. By selecting environment-friendly high-performance raw materials such as the modified XLPE and the nano enhanced thermoplastic elastomer (TPE-N) and accurately controlling the proportion of the raw materials, the insulating material successfully replaces traditional insulating materials containing harmful substances such as polyvinyl chloride (PVC), the environment-friendly standard is met, and the high temperature resistance, the flame retardance and the wear resistance of the power cable are remarkably improved. The innovative application effectively solves the problem that a traditional material is insufficient in performance under a specific application occasion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable preparation, and in particular to a method for preparing a power cable with a high-performance insulation material. Background Art

[0002] With the rapid development of electric vehicles and new energy technologies, power cables play a vital role in power transmission and distribution systems. Especially in the field of new energy vehicles, power cables not only need to have excellent properties such as high current carrying capacity, high temperature resistance, good electromagnetic shielding effect, bending resistance and strong flexibility, but also must ensure stability and safety under long-term work. Therefore, higher requirements are placed on the insulation materials of power cables.

[0003] After searching, the Chinese patent number CN115584097B discloses that the invention discloses a CPVC power cable conduit and a preparation method thereof, wherein the cable conduit is prepared from CPVC resin, polymethyl methacrylate, methacrylic acid-butadiene-styrene copolymer, hyperbranched polymer, stabilizer, filler, compatibilizer, antioxidant and lubricant in a certain ratio as raw materials. The preparation method of the cable conduit is as follows: CPVC resin, polymethyl methacrylate, methacrylic acid-butadiene-styrene copolymer, hyperbranched polymer, stabilizer, filler, compatibilizer, antioxidant and lubricant are mixed evenly, added into a twin-screw extruder after mixing evenly, and after extrusion molding is completed, cooled and shaped to obtain the CPVC power cable conduit. The cable conduit has good processing performance, mechanical properties, low temperature resistance and flame retardant performance, and its service life is greatly improved. The preparation method of the cable conduit is simple, easy to operate and has low preparation cost.

[0004] After searching, the Chinese patent number CN118745274A discloses that the invention discloses a flame-retardant PVC power cable and its preparation method, which belongs to the field of wire and cable technology. 100 parts of PVC resin, 50-60 parts of plasticizer, 40-50 parts of calcium carbonate, 6-10 parts of flame retardant, 5-10 parts of calcium zinc stabilizer, 1-3 parts of coupling agent, 0.8-1.2 parts of lubricant, 0.5-1 parts of antioxidant, 0.5-1 parts of ultraviolet absorber, 0.5-1 parts of colorant, 0.01-0.02 parts of initiator are mixed evenly, heated, stirred, put into a twin-screw extruder for extrusion granulation, melted, extruded, coated on the side of the copper wire, cooled and solidified to obtain a power cable. The flame retardant contains halogen-free flame retardant elements phosphorus, nitrogen and multiple long carbon chains, and there is a chemical reaction between the flame retardant and the polyvinyl chloride resin, so the cable of the invention has efficient and safe flame retardant effect and excellent mechanical properties. The flame retardant works together with other raw materials to make the cable of the present invention have excellent comprehensive performance.

[0005] However, the existing power cable insulation materials mainly include polyvinyl chloride (PVC), cross-linked polyethylene (XLPE), etc. However, PVC contains harmful substances such as lead, which does not meet environmental protection standards and is gradually replaced by environmentally friendly materials such as XLPE. Although XLPE has excellent electrical insulation performance and mechanical strength, in certain specific applications, it is still necessary to further improve its high temperature resistance, flame retardancy and wear resistance. Based on this, the present invention designs a method for preparing a power cable with high-performance insulation materials to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a power cable with a high-performance insulating material, which solves the problem that PVC in the background technology does not meet the standards and has poor performance.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A method for preparing a power cable with a high-performance insulation material, comprising:

[0009] Step A: Raw material selection: select the following environmentally friendly and high-performance raw materials and mix them in the following proportions:

[0010] Modified XLPE (cross-linked polyethylene), 30-40wt%; nano-enhanced thermoplastic elastomer (TPE-N), composed of SEBS (styrene-ethylene-butylene-styrene block copolymer) and 5-10wt% nano-silicon dioxide to enhance wear resistance and mechanical strength: 25-35wt%; flame retardant composition, including antimony trioxide (Sb2O3), aluminum hydroxide (ATH) and decabromodiphenylethane (DBDPE) to synergistically improve the flame retardant properties of the material: 15-20wt%; among which antimony trioxide (Sb2O3) accounts for 6-9wt%, aluminum hydroxide (ATH) accounts for 2-5wt%, and decabromodiphenylethane (DBDPE) accounts for 2-4wt%; antioxidants and anti-ultraviolet agents to extend the service life of the material: each accounts for 0.5-1wt%; processing aids, including lubricants and plasticizers, the total proportion does not exceed 5wt%.

[0011] Step B, preparation process: the above raw materials are premixed in a high-speed mixer, then melt-blended at 180-230°C by a twin-screw extruder, extruded into granules, and vacuum-heat-treated at 120-150°C for 2-3 hours to remove residual volatiles and optimize material properties.

[0012] Step C, preparation of the power cable, including conductor preparation, insulation layer extrusion, cooling and shaping, cabling and shielding, sheath layer extrusion and quality inspection and packaging steps.

[0013] Preferably, in step A, 0.5-1 wt % of dibenzoyl peroxide (BPO) is added to XLPE as a crosslinking agent, and a chemical crosslinking reaction is carried out at 170-190° C. to improve its high temperature resistance.

[0014] Preferably, the step C comprises the following specific steps: step a, conductor preparation, using oxygen-free copper, and making a conductor core wire with a diameter of 2.5-4.0 mm through a wire drawing process; step b, insulation layer extrusion, heating the obtained high-performance insulation material to 200-240°C, and evenly extruding it on the conductor core wire at a constant speed (6-8m / min) through a precision three-layer co-extruder to form an insulation layer with a thickness of 1.2-1.8mm; step c, cooling and shaping, the extruded insulation layer immediately passes through a water cooling system at a cooling rate of 8-12°C / s to ensure that the insulation layer is quickly Curing and maintaining dimensional stability; step d, cabling and shielding, twisting multiple insulated cores into a round cable at a certain pitch, and covering the outer layer with a layer of aluminum-magnesium alloy wire braided mesh as a shielding layer to improve electromagnetic compatibility; step e, sheath extrusion, on the outer layer of the cable after cabling, again extrude a layer of thermoplastic polyurethane (TPU) sheath through an extruder, the thickness of the cable is 2.0-2.5mm, to provide additional wear resistance and environmental adaptability; step f, quality inspection and packaging, the manufactured power cable is comprehensively tested for electrical properties, mechanical properties, flame retardancy, wear resistance and environmental aging resistance.

[0015] It can be seen from the above technical solution that oxygen-free copper with a purity of up to 99.99% is used as raw material, and it is processed into a conductor core wire with a diameter of 2.5-4.0mm through a wire drawing process. Oxygen-free copper can significantly improve the transmission efficiency of the cable and reduce energy loss due to its high conductivity and low resistivity. During the wire drawing process, the diameter of the conductor core wire is uniform and the surface is smooth by precisely controlling the drawing speed and temperature, laying a good foundation for subsequent processing. High-performance insulation materials (such as cross-linked polyethylene or ethylene-vinyl acetate copolymer) are heated to 200-240°C to reach a molten state. Subsequently, the molten insulation is evenly extruded on the conductor core wire at a constant speed (6-8m / min) through a precision three-layer co-extruder to form an insulation layer with a thickness of 1.2-1.8mm. The three-layer co-extrusion technology ensures the uniformity and density of the insulation layer and improves the electrical performance and mechanical strength of the cable.

[0016] Preferably, in the step b, during the extrusion process, a precision temperature control system is used to ensure that the temperature error of each section of the extruder does not exceed ±5°C; before the insulation layer is extruded, a thin layer of silane coupling agent can be pre-coated on the surface of the conductor core wire to enhance the adhesion between the insulation layer and the conductor core wire; in the step f, a comprehensive test is performed to ensure that all indicators comply with the relevant international standards of IEC60332 and IEC 60754, and then the moisture-proof and dust-proof packaging is stored.

[0017] Preferably, the flame retardant grade of the power cable reaches Class A standard of IEC 60332-1, and can maintain excellent electrical insulation performance and mechanical strength under conditions of continuous working temperature up to 90°C and short-term working temperature up to 130°C; the wear resistance of the power cable meets the wear test requirements in the IEC 60811-4-1 standard, that is, under specified conditions, the wear amount does not exceed 0.05g / 1000 revolutions.

[0018] It can be seen from the above technical solution that during the extrusion process of the insulation layer, a precision temperature control system is used to monitor and adjust the temperature of each section of the extruder in real time to ensure that the temperature error of each section does not exceed ±5°C. This precise temperature control ensures the uniform melting and extrusion of the insulation material and avoids uneven quality of the insulation layer caused by temperature fluctuations. Before the insulation layer is extruded, a thin layer of silane coupling agent is pre-coated on the surface of the conductor core wire. As a highly efficient interface modifier, silane coupling agent can significantly improve the adhesion between the insulation layer and the conductor core wire, ensure that the two are closely combined, and improve the overall mechanical strength and electrical performance of the cable.

[0019] Preferably, in the preparation process of the nano-enhanced thermoplastic elastomer (TPE-N) in step A, the nano-silicon dioxide is uniformly dispersed in the SEBS matrix by ultrasonic dispersion technology to ensure that the particle size distribution of the nanoparticles in the TPE-N is uniform and the average particle size does not exceed 50 nanometers, so as to enhance the wear resistance and mechanical strength of the TPE-N; at the same time, the TPE-N is characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) to confirm the chemical bonding and dispersion state between the nanoparticles and the SEBS matrix.

[0020] Preferably, when dibenzoyl peroxide (BPO) is added to XLPE as a crosslinking agent, a high-precision metering pump is used to control the amount of BPO added to ensure that the crosslinking reaction proceeds evenly; during the crosslinking reaction, an online infrared spectrometer (In-line FTIR) is used to monitor the crosslinking degree of XLPE and control the crosslinking degree between 70% and 85% to balance the high temperature resistance and processing performance of the material.

[0021] Preferably, during the extrusion process of the insulating layer in step b, computer-aided design (CAD) software is used to optimize the design of the three-layer co-extrusion die to ensure the thickness uniformity and interface bonding strength between the insulating layer, the semi-conductive shielding layer (if any) and the outer protective layer; at the same time, a laser ranging sensor is used to monitor the extrusion thickness of the insulating layer in real time to control the thickness deviation within ±0.05 mm.

[0022] It can be seen from the above technical scheme that in the preparation process of TPE-N, ultrasonic dispersion technology is first used to evenly disperse nano-silicon dioxide in the SEBS (styrene-ethylene-butylene-styrene block copolymer) matrix using the high-frequency vibration energy of ultrasound. The cavitation effect and micro-jet effect of ultrasound can break the agglomeration between nanoparticles, ensuring that their particle size distribution is uniform and the average particle size does not exceed 50 nanometers. This nanoscale dispersion not only enhances the wear resistance and mechanical strength of TPE-N, but also improves its thermal stability and aging resistance.

[0023] In order to verify the dispersion state and chemical bonding of nanoparticles in TPE-N, the present invention uses Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) for characterization. FTIR can analyze the chemical bond composition in TPE-N and confirm whether chemical bonding is formed between the nanoparticles and the SEBS matrix; SEM can observe the distribution state of nanoparticles in TPE-N and further verify its dispersion uniformity.

[0024] Preferably, in the quality inspection and packaging of step f, a high resistance meter is used to measure the insulation resistance of the power cable to ensure that it is not less than 10^12 ohm·m at 20°C; a universal material testing machine is used to test the tensile strength and elongation at break to ensure that the tensile strength of the insulating layer material is not less than 20 MPa and the elongation at break is not less than 150%; a thermogravimetric analyzer (TGA) is used to evaluate the thermal stability of the material to ensure that its mass loss at 300°C does not exceed 5%; in addition, a smoke density tester is used to evaluate the smoke release when the cable burns to ensure that it meets the low smoke requirements of the IEC 60754-1 standard.

[0025] Preferably, the environmental aging resistance of the power cable is verified by an accelerated aging test, that is, after exposure to 80°C and 85% relative humidity for 168 hours, the dielectric strength and mechanical properties of the insulation layer do not decrease significantly; at the same time, the environmental stress cracking test (ESC) is used to evaluate the cable's resistance to cracking under long-term stress to ensure that no cracking occurs at a specified stress level; in addition, the flame retardant performance of the power cable needs to be verified by a vertical burning test (IEC 60332-3).

[0026] It can be known from the above technical scheme that a high resistance meter is used to measure the insulation resistance of the power cable. The test is carried out at a standard temperature of 20°C to ensure the accuracy and comparability of the test results. Insulation resistance is a key indicator to measure the ability of the cable insulation layer to prevent the passage of current. The present invention requires that the insulation resistance of the power cable be not less than 10^12 ohm·meter. This high standard of insulation resistance can effectively prevent current leakage and ensure the electrical safety of the cable in long-term use. A thermogravimetric analyzer (TGA) is used to evaluate the thermal stability of the cable material. TGA evaluates the thermal stability and thermal decomposition behavior of the material by measuring the mass change of the sample during the programmed temperature increase process. The present invention requires that the mass loss of the cable material at 300°C does not exceed 5% to ensure the reliability and safety of the cable in a high temperature environment.

[0027] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0028] 1. The present invention successfully replaces traditional insulating materials containing harmful substances such as polyvinyl chloride (PVC) by selecting environmentally friendly high-performance raw materials such as modified XLPE and nano-enhanced thermoplastic elastomer (TPE-N) and accurately controlling their proportions. It not only meets environmental protection standards, but also significantly improves the high temperature resistance, flame retardancy and wear resistance of power cables. This innovative application effectively solves the problem of insufficient performance of traditional materials in specific application scenarios and provides strong support for the green development of power cables.

[0029] 2. The present invention optimizes the crosslinking degree of XLPE and balances the high temperature resistance and processing performance of the material through the precise control of a high-precision metering pump and an online infrared spectrometer. This process innovation not only improves the efficiency and repeatability of the crosslinking reaction, but also strengthens the molecular chain structure of XLPE, thereby significantly improving the overall performance of the power cable.

[0030] 3. The present invention verifies the key indicators of the power cable, such as environmental aging resistance, cracking resistance and flame retardant performance, through comprehensive tests such as accelerated aging test and environmental stress cracking test (ESC). These tests not only ensure the stable operation of the cable in harsh environments, but also provide a scientific basis for the design and service life of the cable. In addition, the application of the smoke density tester also ensures the low smoke requirement when the cable burns. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a preparation flow chart of the present invention;

[0032] Figure 2 is a flow chart of the preparation of the power cable of the present invention;

[0033] Figure 3 The present invention is a flow chart of raw material selection. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1;

[0036] See also Figure 1-Figure 3 In the embodiment of the present invention, step A, raw material selection, select the following environmentally friendly and high-performance raw materials, and mix them in the following proportions: modified XLPE (cross-linked polyethylene), 30-40wt%; nano-enhanced thermoplastic elastomer (TPE-N), composed of SEBS (styrene-ethylene-butylene-styrene block copolymer) and 5-10wt% of nano-silicon dioxide to enhance wear resistance and mechanical strength: 25-35wt%; flame retardant composition, including antimony trioxide (Sb2O3), aluminum hydroxide (ATH) and decabromodiphenyl ethane (DBDPE), to synergistically improve the flame retardant properties of the material: 15-20wt%; wherein antimony trioxide (Sb2O3) accounts for 6-9wt%, hydrogen accounts for 10wt%, and decabromodiphenyl ethane accounts for 10wt%. Alumina (ATH) accounts for 2-5wt%, decabromodiphenyl ethane (DBDPE) accounts for 2-4wt%; antioxidants and anti-ultraviolet agents to extend the service life of the material: each accounts for 0.5-1wt%; processing aids, including lubricants and plasticizers, account for no more than 5wt% in total; step B, preparation process: premix the above raw materials in a high-speed mixer, then melt blend at 180-230°C through a twin-screw extruder, extrude granulation, and vacuum heat treat at 120-150°C for 2-3 hours to remove residual volatiles and optimize material properties; step C, preparation of power cables, including conductor preparation, insulation layer extrusion, cooling and shaping, cabling and shielding, sheath layer extrusion and quality inspection and packaging steps.

[0037] In step A, 0.5-1 wt% of dibenzoyl peroxide (BPO) is added to XLPE as a crosslinking agent, and a chemical crosslinking reaction is carried out at 170-190° C. to improve its high temperature resistance.

[0038] As the main component of the cable insulation layer, modified XLPE has excellent electrical properties and high temperature resistance. By adding 0.5-1wt% of dibenzoyl peroxide (BPO) as a cross-linking agent and conducting a chemical cross-linking reaction at 170-190°C, its high temperature resistance and mechanical strength can be further improved. Nano-enhanced thermoplastic elastomer (TPE-N) is composed of SEBS (styrene-ethylene-butylene-styrene block copolymer) and 5-10wt% of nano-silica. The wear resistance and mechanical strength of the material are significantly improved through the reinforcement effect of nanoparticles. Flame retardant composition: Contains antimony trioxide (Sb2O3), aluminum hydroxide (ATH) and decabromodiphenyl ethane (DBDPE). These flame retardants effectively improve the flame retardant properties of the material through synergistic effects and reduce the risk of combustion of the cable in a fire. Antioxidants and UV inhibitors can extend the service life of the material and prevent material aging caused by oxidation and ultraviolet radiation.

[0039] Step C includes the following specific steps: step a, conductor preparation, using oxygen-free copper, and making a conductor core wire with a diameter of 2.5-4.0 mm through a wire drawing process; step b, insulation layer extrusion, heating the obtained high-performance insulation material to 200-240°C, and evenly extruding it on the conductor core wire at a constant speed (6-8m / min) through a precision three-layer co-extruder to form an insulation layer with a thickness of 1.2-1.8mm; step c, cooling and shaping, the extruded insulation layer immediately passes through a water cooling system at a cooling rate of 8-12°C / s to ensure that the insulation layer is quickly solidified and Keep the size stable; Step d, cabling and shielding, twist multiple insulated wire cores into a round cable at a certain pitch, and coat the outer layer with a layer of aluminum-magnesium alloy wire braided mesh as a shielding layer to improve electromagnetic compatibility; Step e, sheath layer extrusion, on the outer layer of the cable after cabling, again extrude a layer of thermoplastic polyurethane (TPU) sheath through an extruder, with a thickness of 2.0-2.5mm, to provide additional wear resistance and environmental adaptability; Step f, quality inspection and packaging, conduct comprehensive tests on the electrical properties, mechanical properties, flame retardant properties, wear resistance and environmental aging resistance of the manufactured power cable. In step b, during the extrusion process, a precision temperature control system is used to ensure that the temperature error of each section of the extruder does not exceed ±5°C; before the insulation layer is extruded, a thin layer of silane coupling agent can be pre-coated on the surface of the conductor core wire to enhance the adhesion between the insulation layer and the conductor core wire; In step f, after comprehensive testing to ensure that all indicators meet the relevant international standards of IEC 60332 and IEC 60754, moisture-proof and dust-proof packaging and storage are carried out.

[0040] After the cable is completed, a layer of thermoplastic polyurethane (TPU) sheath with a thickness of 2.0-2.5mm is extruded on the outer layer of the cable through an extruder. The TPU sheath has excellent wear resistance and environmental adaptability, which can protect the cable from damage by the external environment and extend the service life of the cable. The finished power cable undergoes comprehensive quality inspection, including tests on electrical properties, mechanical properties, flame retardancy, wear resistance and environmental aging resistance. All tests must comply with the requirements of relevant international standards such as IEC 60332 and IEC 60754. After passing the test, the cable is stored in moisture-proof and dust-proof packaging to ensure the safety and reliability of the cable during storage and transportation.

[0041] The working principle of the embodiment of the present invention is: in the raw material proportioning stage, modified XLPE is used as the main material, and dibenzoyl peroxide (BPO) is added as a cross-linking agent to carry out a chemical cross-linking reaction at 170-190°C. This reaction not only enhances the high temperature resistance of XLPE, but also provides it with stable physical and chemical properties. At the same time, the introduction of nano-enhanced thermoplastic elastomer (TPE-N) disperses nano-silicon dioxide evenly in the SEBS matrix through ultrasonic dispersion technology, which significantly improves the wear resistance and mechanical strength of the material. The precise proportion of the flame retardant composition, including antimony trioxide (Sb2O3), aluminum hydroxide (ATH) and decabromodiphenyl ethane (DBDPE), synergistically improves the flame retardant properties of the material.

[0042] In the preparation process of power cables, the preparation of oxygen-free copper conductor core wire is the basis. It is made into a core wire with a diameter of 2.5-4.0mm through a wire drawing process, which ensures the conductivity and mechanical strength of the conductor. The extrusion of the insulation layer is a key step. After the high-performance insulation material is heated to 200-240℃, it is evenly extruded on the conductor core wire at a constant speed through a precision three-layer co-extruder to form an insulation layer with a thickness of 1.2-1.8mm. During the extrusion process, the precision temperature control system ensures the stability of the extrusion temperature, and the silane coupling agent pre-coated on the surface of the conductor core wire enhances the adhesion between the insulation layer and the conductor core wire. During the cooling and shaping stage, the extruded insulation layer immediately passes through a water cooling system and is rapidly solidified at a cooling rate of 8-12℃ / s. This process ensures the dimensional stability and physical properties of the insulation layer. Subsequently, multiple insulated cores are twisted into a round cable at a certain pitch, and the outer layer is coated with a layer of aluminum-magnesium alloy wire braided mesh as a shielding layer.

[0043] Embodiment 2;

[0044] See also Figure 1-Figure 3In the embodiment of the present invention, the flame retardant grade of the power cable reaches the Class A standard of IEC 60332-1, and can maintain excellent electrical insulation performance and mechanical strength under the conditions of continuous working temperature up to 90°C and short-term working temperature up to 130°C; the wear resistance of the power cable meets the wear test requirements of the IEC 60811-4-1 standard, that is, under the specified conditions, the wear amount does not exceed 0.05g / 1000 revolutions. In the preparation process of the nano-enhanced thermoplastic elastomer (TPE-N) in step A, the nano-silicon dioxide is uniformly dispersed in the SEBS matrix by ultrasonic dispersion technology to ensure that the particle size distribution of the nanoparticles in TPE-N is uniform and the average particle size does not exceed 50 nanometers, so as to enhance the wear resistance and mechanical strength of TPE-N; at the same time, the TPE-N is characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) to confirm the chemical bonding and dispersion state between the nanoparticles and the SEBS matrix.

[0045] When adding benzoyl peroxide (BPO) as a crosslinking agent to XLPE, a high-precision metering pump is used to control the amount of BPO added to ensure that the crosslinking reaction proceeds evenly. During the crosslinking reaction, an online infrared spectrometer (In-line FTIR) is used to monitor the crosslinking degree of XLPE and control the crosslinking degree between 70% and 85% to balance the material's high temperature resistance and processing performance.

[0046] When adding dibenzoyl peroxide (BPO) as a crosslinking agent to XLPE (crosslinked polyethylene), the present invention uses a high-precision metering pump to accurately control the amount of BPO added to ensure that the crosslinking reaction can proceed evenly. During the crosslinking reaction, an online infrared spectrometer (In-line FTIR) is used to monitor the crosslinking degree of XLPE in real time, and the crosslinking degree is controlled between 70% and 85% by adjusting the crosslinking conditions (such as temperature, time, etc.). This step not only ensures that XLPE has excellent high temperature resistance, but also takes into account its good processing performance, providing a high-quality material foundation for subsequent cable manufacturing.

[0047] The working principle of the embodiment of the present invention is: in the cross-linking modification process of XLPE, a high-precision metering pump plays a vital role. The pump ensures the uniformity of the cross-linking reaction by accurately controlling the amount of dibenzoyl peroxide (BPO) added, avoiding the degradation of material performance caused by excessive or insufficient cross-linking agent. At the same time, the real-time monitoring function of the online infrared spectrometer (In-line FTIR) is used to monitor the cross-linking degree of XLPE to ensure that the cross-linking degree is maintained within the range of 70%-85%. This precise control not only balances the high temperature resistance and processing performance of the material, but also improves the efficiency and repeatability of the cross-linking reaction. By optimizing the cross-linking degree, the molecular chain structure of XLPE is effectively strengthened.

[0048] In the preparation process of power cables, these high-performance materials are carefully combined and processed into finished products. First, the oxygen-free copper conductor core wire treated by the wire drawing process is used as the core part of the cable to ensure good conductivity and mechanical strength. Subsequently, the high-performance insulation material is heated to a suitable temperature and evenly extruded on the conductor core wire by a precision three-layer co-extruder to form an insulation layer with precisely controlled thickness.

[0049] Embodiment 3;

[0050] See also Figure 1-Figure 3 In the embodiment of the present invention, during the extrusion process of the insulating layer in step b, computer-aided design (CAD) software is used to optimize the design of the three-layer co-extrusion die to ensure the thickness uniformity and interface bonding strength between the insulating layer, the semi-conductive shielding layer (if any) and the outer protective layer; at the same time, a laser ranging sensor is used to monitor the extrusion thickness of the insulating layer in real time to control the thickness deviation within ±0.05 mm.

[0051] In step f, during quality inspection and packaging, a high resistance meter is used to measure the insulation resistance of the power cable to ensure that it is not less than 10^12 ohm·m at 20°C; a universal material testing machine is used to test the tensile strength and elongation at break to ensure that the tensile strength of the insulating layer material is not less than 20 MPa and the elongation at break is not less than 150%; a thermogravimetric analyzer (TGA) is used to evaluate the thermal stability of the material to ensure that its mass loss at 300°C does not exceed 5%; in addition, a smoke density tester is used to evaluate the smoke release when the cable burns to ensure that it meets the low smoke requirements of the IEC 60754-1 standard.

[0052] The environmental aging resistance of power cables is verified through accelerated aging tests, that is, after exposure to 80°C and 85% relative humidity for 168 hours, there is no significant decrease in the dielectric strength and mechanical properties of the insulation layer; at the same time, the environmental stress cracking test (ESC) is used to evaluate the cable's resistance to cracking under long-term stress to ensure that no cracking occurs at the specified stress level; in addition, the flame retardant performance of power cables must also be verified through a vertical burning test (IEC 60332-3).

[0053] The insulation resistance of the power cable is measured using a high resistance meter. The test is performed at a standard temperature of 20°C to ensure the accuracy and comparability of the test results. Insulation resistance is a key indicator for measuring the ability of the cable insulation layer to prevent the passage of current. The present invention requires that the insulation resistance of the power cable be no less than 10^12 ohm·meter. This high standard of insulation resistance can effectively prevent current leakage and ensure the electrical safety of the cable during long-term use. A thermogravimetric analyzer (TGA) is used to evaluate the thermal stability of the cable material. TGA evaluates the thermal stability and thermal decomposition behavior of the material by measuring the mass change of the sample during the programmed temperature increase process. The present invention requires that the mass loss of the cable material at 300°C does not exceed 5% to ensure the reliability and safety of the cable in a high temperature environment.

[0054] The working principle of the embodiment of the present invention is: in the quality inspection and packaging links, a variety of high-precision testing equipment is used to ensure that the various performance indicators of the cable meet international standards. The application of the high resistance meter can accurately measure the insulation resistance of the power cable at 20°C to ensure that it is not less than 10^12 ohm·meter, thereby ensuring the electrical insulation performance of the cable. The tensile strength and elongation at break tests of the universal material testing machine can evaluate the mechanical properties of the insulating layer material to ensure that its tensile strength is not less than 20MPa and the elongation at break is not less than 150%, which provides a strong guarantee for the durability and safety of the cable. The evaluation of the thermogravimetric analyzer (TGA) can reveal the thermal stability of the material at 300°C and ensure that the mass loss does not exceed 5%, which is crucial for the stable operation of the cable in a high temperature environment. In addition, the application of the smoke density tester can evaluate the amount of smoke released when the cable burns to ensure that it meets the low smoke requirements of the IEC 60754-1 standard.

[0055] In terms of environmental aging resistance verification, the introduction of accelerated aging tests and environmental stress cracking tests (ESC) further improves the long-term reliability of cables. The accelerated aging test simulates the aging process of cables in harsh environments by exposing them to 80°C and 85% relative humidity for 168 hours, ensuring that there is no significant decrease in the dielectric strength and mechanical properties of the insulation layer. This test not only verifies the weather resistance of the cable, but also provides a scientific basis for the design and service life of the cable. The environmental stress cracking test (ESC) evaluates the cable's ability to resist cracking under long-term stress.

[0056] Working principle: First, by selecting environmentally friendly high-performance raw materials such as modified XLPE, nano-enhanced thermoplastic elastomer (TPE-N), flame retardant composition, and precisely controlling their proportions, the material's high temperature resistance, flame retardancy, wear resistance and other characteristics are achieved. During the preparation process, ultrasonic dispersion technology, high-precision metering pumps, online infrared spectrometers and other technical means are used to ensure the uniformity of the material structure and the stability of the performance. The preparation of power cables is carried out through precise three-layer co-extrusion, cooling and shaping, cable shielding and other steps, combined with computer-aided design and laser ranging sensing technology to ensure the thickness uniformity and interface bonding strength of the insulation layer and the sheath. Finally, through quality inspection and packaging links, high-precision testing equipment is used to comprehensively evaluate the various performance indicators of the cable to ensure that it meets international standards. The entire process focuses on the environmental protection of raw materials, the accuracy of preparation and the reliability of products.

[0057] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit thereof, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a power cable with high-performance insulation material, characterized in that: include: Step A: Raw material selection: select the following environmentally friendly and high-performance raw materials and mix them in the following proportions: Modified XLPE (cross-linked polyethylene), 30-40wt%; Nano-enhanced thermoplastic elastomer (TPE-N), made of SEBS (styrene-ethylene-butylene-styrene block copolymer) compounded with 5-10wt% nano-silica to enhance wear resistance and mechanical strength: 25-35wt%; A flame retardant composition comprising antimony trioxide (Sb2O3), aluminum hydroxide (ATH) and decabromodiphenylethane (DBDPE) to synergistically improve the flame retardancy of the material: 15-20wt%; wherein antimony trioxide (Sb2O3) accounts for 6-9wt%, aluminum hydroxide (ATH) accounts for 2-5wt%, and decabromodiphenylethane (DBDPE) accounts for 2-4wt%; Antioxidants and anti-ultraviolet agents to extend the service life of the material: 0.5-1wt% each; Processing aids, including lubricants and plasticizers, not exceeding 5wt% in total; Step B, preparation process: the above raw materials are premixed in a high-speed mixer, then melt-blended at 180-230° C. by a twin-screw extruder, extruded into granules, and vacuum-heat-treated at 120-150° C. for 2-3 hours to remove residual volatiles and optimize material properties; Step C, preparation of the power cable, including conductor preparation, insulation layer extrusion, cooling and shaping, cabling and shielding, sheath layer extrusion and quality inspection and packaging steps.

2. The method for preparing a power cable having a high-performance insulating material according to claim 1, characterized in that: In the step A, 0.5-1 wt% of dibenzoyl peroxide (BPO) is added to XLPE as a crosslinking agent, and a chemical crosslinking reaction is carried out at 170-190° C. to improve its high temperature resistance.

3. The method for preparing a power cable with a high-performance insulation material according to claim 1, characterized in that: The step C comprises the following specific steps: Step a, conductor preparation, using oxygen-free copper, and making a conductor core wire with a diameter of 2.5-4.0 mm through a wire drawing process; Step b, extruding the insulating layer, heating the obtained high-performance insulating material to 200-240° C., and evenly extruding it onto the conductor core wire at a constant speed (6-8 m / min) through a precision three-layer co-extruder to form an insulating layer with a thickness of 1.2-1.8 mm; Step c, cooling and shaping, the extruded insulation layer immediately passes through a water cooling system at a cooling rate of 8-12°C / s to ensure that the insulation layer solidifies quickly and maintains dimensional stability; Step d, cabling and shielding, twisting multiple insulated wire cores into a round cable at a certain pitch, and covering the outer layer with a layer of aluminum-magnesium alloy wire braided mesh as a shielding layer to improve electromagnetic compatibility; Step e, extrusion of the sheath layer: on the outer layer of the cable after cabling, a layer of thermoplastic polyurethane (TPU) sheath is extruded again by an extruder, with a thickness of 2.0-2.5 mm, to provide additional wear resistance and environmental adaptability; Step f, quality inspection and packaging, conduct comprehensive tests on the electrical properties, mechanical properties, flame retardancy, wear resistance and environmental aging resistance of the manufactured power cable.

4. The method for preparing a power cable with a high-performance insulation material according to claim 3, characterized in that: In the step b, during the extrusion process, a precision temperature control system is used to ensure that the temperature error of each section of the extruder does not exceed ±5°C; Before the insulation layer is extruded, a thin layer of silane coupling agent may be pre-coated on the surface of the conductor core wire to enhance the adhesion between the insulation layer and the conductor core wire; in the step f, a comprehensive test is performed to ensure that all indicators comply with the relevant international standards of IEC 60332 and IEC 60754, and then the moisture-proof and dust-proof packaging is carried out for storage.

5. The method for preparing a power cable with a high-performance insulation material according to claim 1, characterized in that: The flame retardant grade of the power cable reaches Class A standard of IEC 60332-1, and can maintain excellent electrical insulation performance and mechanical strength under conditions of continuous working temperature up to 90°C and short-term working temperature up to 130°C; the wear resistance of the power cable meets the wear test requirements of IEC 60811-4-1 standard, that is, under specified conditions, the wear amount does not exceed 0.05g / 1000 revolutions.

6. The method for preparing a power cable with a high-performance insulation material according to claim 1, characterized in that: In the preparation process of the nano-enhanced thermoplastic elastomer (TPE-N) in step A, the nano-silicon dioxide is uniformly dispersed in the SEBS matrix by using ultrasonic dispersion technology to ensure that the particle size distribution of the nanoparticles in the TPE-N is uniform and the average particle size does not exceed 50 nanometers, so as to enhance the wear resistance and mechanical strength of the TPE-N; at the same time, the TPE-N is characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) to confirm the chemical bonding and dispersion state between the nanoparticles and the SEBS matrix.

7. The method for preparing a power cable with a high-performance insulation material according to claim 2, characterized in that: When adding benzoyl peroxide (BPO) as a crosslinking agent to XLPE, a high-precision metering pump is used to control the amount of BPO added to ensure that the crosslinking reaction proceeds evenly. During the crosslinking reaction, an online infrared spectrometer (In-line FTIR) is used to monitor the crosslinking degree of XLPE and control the crosslinking degree between 70% and 85% to balance the material's high temperature resistance and processing performance.

8. The method for preparing a power cable with a high-performance insulation material according to claim 3, characterized in that: During the extrusion process of the insulating layer in step b, computer-aided design (CAD) software is used to optimize the design of the three-layer co-extrusion die to ensure the thickness uniformity and interface bonding strength between the insulating layer, the semi-conductive shielding layer (if any) and the outer protective layer; at the same time, a laser ranging sensor is used to monitor the extrusion thickness of the insulating layer in real time to control the thickness deviation within ±0.05 mm.

9. The method for preparing a power cable with a high-performance insulation material according to claim 4, characterized in that: In the quality inspection and packaging of step f, a high resistance meter is used to measure the insulation resistance of the power cable to ensure that it is not less than 10^12 ohm·m at 20°C; a universal material testing machine is used to test the tensile strength and elongation at break to ensure that the tensile strength of the insulating layer material is not less than 20 MPa and the elongation at break is not less than 150%; a thermogravimetric analyzer (TGA) is used to evaluate the thermal stability of the material to ensure that its mass loss at 300°C does not exceed 5%; in addition, a smoke density tester is used to evaluate the smoke release when the cable burns to ensure that it meets the low smoke requirements of the IEC 60754-1 standard.

10. The method for preparing a power cable with a high-performance insulation material according to claim 5, characterized in that: The environmental aging resistance of the power cable is verified by an accelerated aging test, that is, after exposure for 168 hours at 80°C and 85% relative humidity, there is no significant decrease in the dielectric strength and mechanical properties of the insulation layer; At the same time, the environmental stress cracking test (ESC) is used to evaluate the cable's resistance to cracking under long-term stress to ensure that no cracking occurs under the specified stress level; in addition, the flame retardant performance of the power cable must be verified through a vertical burning test (IEC 60332-3).

Citation Information

Patent Citations

  • A CPVC power cable conduit and preparation method thereof

    CN115584097B

  • Flame-retardant PVC power cable and preparation method thereof

    CN118745274A